THE DEVELOPMENT OF THE QUALITY OF COMMUNITY RESOURCES IN THE BORDER AREA. ( A Research in the Marore Islands Sub-District of Sangihe Islannds Regency) - PUTRI, DEWI AMBARWATI; TULUSAN, FEMMY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
This research aims to explain the development of the quality of community resources in the border area ofMarore Islands Sub-District in Sangihe Islands Regency. The program of developing the quality ofcommunity resources of the border area in the Marore Islands Sub-District of Sangihe Island Regency iscarried out by the Planning and Research and Development Agency (BAPELITBANG) of the SangiheIslands Regency. This research uses descriptive method of qualitative approach, and data collectiontechnique done by observation, interview technique and documentation. Number of informants as many as10 people. In this research using indicators of quality development of human resources according toNotoatmodjo, which in this process approach includes 2 indicators as follows; (1) education and (2) training.The result of the research shows that the development of the quality of border area community in MaroreIslands Sub-District is quite good. This can be seen from the existing education programs and trainingprograms in the border areas to develop the quality of community resources in the border areas. But thereare still some obstacles related to such programs such as the lack of educators so that the utilization ofexisting facilities has not been maximized. Other obstacles include the lack of public interest to participatein that programs.Key words: Development, Quality of Human Resources, Border Area